The Effect of Prenatal Yoga on Emesis Gravidarum in the First Trimester Pregnant Women - Sri Mahmut Ambar Wati; Nila Widya Keswara; Rifzul Maulina (Health Dynamics, 2024)
Background: Increased levels of progesterone, estrogen, and HCG (chorionic gonadotropin hormone) during the first trimester of pregnancy can produce morning sickness, also known as emesis gravidarum (nausea and vomiting). To lessen the release of hormones that induce anxiety, severe nausea, and vomiting, prenatal yoga practitioners can block the stimulation of sympathetic nerves by practicing muscle relaxation. This study aims to ascertain how prenatal yoga affects first-trimester emesis gravidarum. Method: This study used a pre-experimental design with a pretest-posttest design in one group, involving 16 mothers who had emesis gravidarum at PMB Fatimah Bandung Rejosari, Sukun, Malang. Data collection was done using the questionnaire. Results: The result was that two prenatal yoga sessions over two weeks demonstrated significant benefits. Prenatal yoga affects emesis gravidarum in the first trimester of pregnancy, as indicated by the independent t-test technique (2-tailed) of 0.000 <0.005. Discussion: Steroid hormones can slow down stomach emptying, which causes emesis gravidarum. Excessive or low cortisol levels can be brought back to normal with yoga. Yoga offers numerous mental and physical health advantages. Conclusion We can conclude that the course of treatment impacts the severity of emesis gravidarum, or nausea and vomiting, during the first trimester of pregnancy.